Rhodes Fruit Farms: A small beginning in the Paarl Valley 1897-1910 - Chris Aucamp (Contree)
Rhodes Fruit Farms, situated in the Great Drakenstein Valley, was established in 1897 by Harry Pickstone with the financial aid of Cecil John Rhodes. Pickstone saw the potential for the large scale production and export of deciduous fruit at the Cape. Under his guidance a company was floated. Various farms purchased and the fruit industry placed on a scientific and profitable foundation. From a humble beginning Rhodes Fruit Farms made an important contribution to the advancement and development of the fresh fruit industry in South Africa.